Penemuan Hukum Sebagai Implementasi Teori Hukum Dalam Menjawab Kekosongan Norma - Indah, Reviana Mutiara; Triadi, Irwan (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This research is motivated by the gap between static positive law and the continuously evolving dynamics of society, which often creates a legal vacuum (rechts vacuum). This condition requires judges to abandon the old paradigm of being merely the